Modulation of viscosity, microstructure and lipolysis of W/O emulsions by cellulose ethers during in vitro digestion in the dynamic and semi-dynamic gastrointestinal models. (July 2022) - Iqbal, Shahid; Zhang, Ping; Wu, Peng; Yin, Quanyi; Hidayat, Khemayanto; Chen, Xiao Dong
Abstract: In this study, W/O emulsions incorporated with various proportions of two hydrocolloids, namely, methylcellulose (MC) and hydroxypropyl methylcellulose (HPMC), were prepared. The shear viscosity, microstructure, and lipolysis of the W/O emulsions before and during in vitro digestion in the dynamic (DIVHS) and semi-dynamic gastrointestinal models were evaluated and compared. The shear viscosity of both emulsions increased with the addition of MC and HPMC content up to a certain limit (0.5–2%), whereas it significantly decreased at a higher addition level (4%) due to the increased flocculation and coalescence in higher cellulose ethers. The HPMC emulsions (2 wt % in aqueous phases) showed higher viscosity and larger droplet size than the equivalent MC emulsions before and during simulated digestion, accompanied by the lower extent of lipolysis. These results are in line with the formation of a more compact and stronger gel structure in HPMC emulsions, which could retard lipase adsorption at the W–O interface. For both emulsions at the same concentration (40 wt%), a higher extent of free fatty acid (FFA) release was found during digestion in the dynamic system (HPMC ꞊ 62%, MC ꞊ 72%) compared to that in the semi-dynamic model (HPMC ꞊ 58%, MC ꞊ 70%). This behavior was supported by the smaller droplet size of emulsions digesta collected from the dynamic system having a larger surface area. Overall, the present study suggested that the dynamic DIVHS system was more effective in enzymatic hydrolysis of the W/O emulsions investigated than the semi-dynamic model under the current experimental conditions. This work had provided valuable insights into the modulation of the structural and digestive properties of W/O emulsions by the addition of MC and HPMC, which could be meaningful for the development of healthier emulsion-based food products ( e.g ., margarine and spreads) with reduced lipid digestibility. Graphical abstract: Image 1 Highlights: Methylcellulose (MC) and hydroxypropyl methylcellulose (HPMC) used to fortify W/O emulsions. Viscosity of emulsions increased with increasing MC and HPMC addition (0.5–2%). HPMC emulsions showed higher viscosity than MC emulsions before and after GIT digestion. More compact and stronger gel structure in HPMC emulsions supported the lower lipolysis. Higher digesta viscosity and slower FFAs release in DVHS than that in the semi-dynamic model.